2009
DOI: 10.1002/app.29500
|View full text |Cite
|
Sign up to set email alerts
|

PET/EVA/PP ternary blends: An investigation of extended morphological properties

Abstract: In this study, the effects of different parameters on the morphological properties of ternary blends were investigated. Therefore two systems (PET/ H-EVA/PP and PET/L-EVA/PP, H-EVA and L-EVA are high and low viscosity, respectively) were prepared by melt mixing process. In all of the blends, poly (ethylene terephthalate) (PET) as the major phase-with poly propylene (PP) and two grades of poly (ethyl-stat-vinylacetate) (EVA) with different viscosities and subsequently different interfacial interactions was blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…To answer this question, both types of the parameters controlling the formation of morphology in the ternary blend systems should be considered: thermodynamic parameters (interfacial tensions) and kinetic factors (viscosity and/or elasticity). Considering the researches carried out in the field of ternary blends, [3,4,[10][11][12][13][14][15][16] it could be proposed that the primary governing factor for the formation of the phase structure is the interfacial tensions of the pairs of polymers present in the blend, and the system tends to form a morphology that minimizes interfaces with high interfacial tension. However, if there does not exist a significant thermodynamic driving force, as happened for PA6/SAN2/SEBS-g-MAH, then the kinetics could play a meaningful role and change the morphology against the prediction based on the interfacial tensions of components.…”
Section: Morphological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, both types of the parameters controlling the formation of morphology in the ternary blend systems should be considered: thermodynamic parameters (interfacial tensions) and kinetic factors (viscosity and/or elasticity). Considering the researches carried out in the field of ternary blends, [3,4,[10][11][12][13][14][15][16] it could be proposed that the primary governing factor for the formation of the phase structure is the interfacial tensions of the pairs of polymers present in the blend, and the system tends to form a morphology that minimizes interfaces with high interfacial tension. However, if there does not exist a significant thermodynamic driving force, as happened for PA6/SAN2/SEBS-g-MAH, then the kinetics could play a meaningful role and change the morphology against the prediction based on the interfacial tensions of components.…”
Section: Morphological Studymentioning
confidence: 99%
“…This model has been used frequently by researchers for the prediction of the morphology of ternary blends. [3][4][9][10][11][12][13][14] It is worth mentioning that there is another complex morphology that has received less attention. It consists of the core-shell morphology together with dispersed particles of the shell-forming component.…”
Section: Introductionmentioning
confidence: 99%
“…EVA was chosen due to the wide processing window and suitable processing temperature (30–110°C) in combination with TPP at which thermo‐degradation can be avoided or reduced. In other studies EVA was blended with different polymers such as high‐density polyethylene (PE‐HD), low‐density polyethylene (PE‐LD), ground tyre rubber, polypropylene (PP), poly(ethyleneterephthalate) (PET), and polyamide 6 (PA6) as well as with nanoclays which indicates that EVA is well suitable for blending with other polymers and particles …”
Section: Introductionmentioning
confidence: 98%
“…In other studies EVA was blended with different polymers such as high-density polyethylene (PE-HD), low-density polyethylene (PE-LD), ground tyre rubber, polypropylene (PP), poly(ethyleneterephthalate) (PET), and polyamide 6 (PA6) as well as with nanoclays which indicates that EVA is well suitable for blending with other polymers and particles. [28][29][30][31][32][33][34][35] Previous studies have, however, already demonstrated the suitability of whey protein formulations for packaging materials. Consequently, the objective of this study was to investigate the technofunctional properties of up to now not studied thermoplastic whey protein containing blends for food packaging based on TPP and EVA.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending has been widely used in the industry as a facile method at a relatively lower cost compared with the synthesis of a new polymer . It is well‐known that the mechanical properties of ternary blends of immiscible polymers are highly affected by the final morphology of the ternary system, size of dispersed phases, and also the order of interaction and adhesion between different phases .…”
Section: Introductionmentioning
confidence: 99%